Making meaning of voluntary medical adult male circumcision (VMAMC) in the context of HIV prevention in Johannesburg, South Africa - Howard-Payne, Lynlee (My University, 2015)
Male circumcision (MC) serves a number of functions, which have traditional; aesthetic; and/or medical significance in South Africa. Recent studies have found that voluntary medical adult male circumcision (VMAMC) offers significant protection against HIV infection. Although the South African government has initiated a selective and staggered rollout of this HIV intervention, no empirical data are available on the meanings that key individuals attach to VMAMC. Such meanings are bound to the way that VMAMC will be received as a public health intervention. As such, this study aimed to develop a substantive grounded theory of how key stakeholders make meaning of VMAMC in the context of HIV prevention in South Africa to better understand the psychosocial factors that impact public health responses to this HIV intervention. A Straussian grounded theory approach was utilised to analyse the repeated semi-structured interview data gathered from 30 adult male participants who live or work near the Alexandra Informal Settlement in Johannesburg, South Africa. These participants were from diverse racial, religious, and cultural backgrounds, each with their own unique practices regarding traditional circumcision or non-circumcision. The resulting grounded theory generated tensions between tradition and medicine as a core category. This category is comprised of three emerging sub-categories that impact VMAMC meanings, namely (1) citizen rights and responsibilities in times of HIV, (2) men's health, and (3) the politics of implementation. These categories are tensioned between plurality and fusion, to result in seemingly dual responses to the basic social problem of performing masculinity in the context of HIV prevention in South Africa. The overarching basic social process, negotiating tensions between tradition and medicine is driven by a perceived crisis of medicalised modernity. This crisis is made possible by an attempt to negotiate the meanings of traditional circumcisions that are most generally performed by community leaders and traditional healers at initiation schools in rural parts of South Africa to impart powerful masculine qualities to young men, against the health generating benefits of VMAMC when performed in clinical, surgical conditions by a medical doctor. Despite public health based behavioural and biological interventions, HIV remains a pressing health burden in South Africa. While psycho-educational intervention programmes dominate the intervention landscape in South Africa, the importance of the meanings individuals attach to behavioural and body directed interventions has been frequently overlooked. This study, however; proposes that understanding the meanings attached to what appears to be a simple once-off body directed intervention is imperative to the development, roll-out, upscaling, monitoring and evaluation of VMAMC and all other HIV prevention strategies.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2014